Diverse electronic, magnetic, optical and electronic transport properties of the penta-NiN2 nanoribbons: A frst-principles investigation - Dang, Nguyen Hai; Thao, Pham Thi Bich; Thanh, Thai Van; Tien, Nguyen Thanh (Communications in Physics, 2025)
In this work, the structural, electronic, optical, and electronic transport properties of the p-NiN2 nanoribbons with four typical edge shapes of armchair–armchair (AA), sawtooth–sawtooth (SS), zigzag–armchair (ZA), and zigzag–zigzag (ZZ) are fully revealed by the key quantities developed from DFT calculations, including the formation energies, structural parameters, spin splitting electronic band structures, atom-projected density of states (PDOS), spatial spin density distribution, optical absorption spectra, I-V curves, transmission functions (T(E)), and spin filtering efficiency. As a result, all the p-NiN2NR systems achieve a good structural stability. On the electronic characteristics, only the ZA8 configuration behaves as a ferromagnetic half-metal, while the other configurations all belong to ferromagnetic semiconductors. The origin of the magnetism is clarified by the spatial spin density distribution. The optical absorption spectra of the penta-NiN2 nanoribbon indicates that the absorption spectral region can be sensitively controlled by the widths and edge shapes. The I-V spectra evidence that the negative differential characteristics and the spin filtering efficiency appear in the DAA7, DSS7, and DZA6 configurations, and only disappear in the DZZ7 configuration. The transmission function (T(E)) of the DAA7-up and the DSS7-up configurations shows a stronger negative differential effect than that of the DZA6-up and DZZ7-up configurations. In addition, the spin filtering efficiency (SFE) of the DAA7 and DSS7 configurations is much higher than that of the DZA6 and DZZ7 configurations. The essential electronic, optical, and electronic transport properties of the p-NiN2 nanoribbons controlled by edge shapes and widths are very promising for next-generation electronic, optoelectronic, and spintronic applications.